1990
DOI: 10.1111/j.1346-8138.1990.tb03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cutaneous T‐cell Lymphomas (CTCL) with Extracorporeal Photochemotherapy

Abstract: Since August of 1988, we have treated seven CTCL patients with extracorporeal photochemotherapy, including two with tumor-stage mycosis fungoides (MF) showing mucinous degeneration, two with plaque-stage MF, and two with erythrodermatous MF. One was withdrawn just after the first trial. For each patient, the phenotypes of peripheral blood lymphocytes were analyzed by flow cytometry in terms of the percentages of OKT11, OKT3, OKT4, Leu9, OKT8, B1, Tac, OKT9, OKIa1, Leu7, Leu3a/4B4, and Leu3a/2H4 cells. These pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The results of our study have shown that the median Skindex-29 score was decreased by 42% (from 88 to 51), after the application of ECP. A corresponding improvement between 40-50% has also been recorded by other retrospective studies [19][20][21][22][23][24][25]. The observed improvement in the Skindex-29 score mainly results from the improvement of the symptoms (questions 3, 10, 19, 28) and less from the improvement of the patients' functionality (questions 2, 29).…”
Section: Discussionsupporting
confidence: 72%
“…The results of our study have shown that the median Skindex-29 score was decreased by 42% (from 88 to 51), after the application of ECP. A corresponding improvement between 40-50% has also been recorded by other retrospective studies [19][20][21][22][23][24][25]. The observed improvement in the Skindex-29 score mainly results from the improvement of the symptoms (questions 3, 10, 19, 28) and less from the improvement of the patients' functionality (questions 2, 29).…”
Section: Discussionsupporting
confidence: 72%
“…Other studies have been published since the initial report, with similar results: responses greater than 75% was observed in 5 out of 32 patients (Heald, 1989), 1 out of 8 patients (Armus, 1990), and in 2 out of 7 patients in the latest published report (Nagatani, 1990).…”
Section: -4 Clinical Use Of Extracorporeal Photochemotherapy 2-4-1supporting
confidence: 60%